Transcontinental Dispersal of Nonendemic Fungal Pathogens through Wooden Handicraft Imports - Jason A. Smith; Tania Quesada; Gideon Alake; Nicolas Anger (mBio, 2022)
ABSTRACT This study examined the viability and diversity of fungi harbored in imported wooden handicraft products sold in six retail stores in Florida, United States. Despite being subjected to trade regulations that require various sterilization/fumigation protocols, our study demonstrates high survival and diversity of fungi in wood products originating from at least seven countries on three continents. Among these fungi were nonendemic plant and human pathogens, as well as mycotoxin producers. Several products that are sold for use in food preparation and consumption harbored a novel (to North America) plant and human pathogen, Paecilomyces formosus. In addition, a high number of species isolated were thermophilic and included halophilic species, suggesting adaptability and selection through current wood treatment protocols that utilize heat and/or fumigation with methyl-bromide. This research suggests that current federal guidelines for imports of wooden goods are not sufficient to avoid the transit of potential live pathogens and demonstrates the need to increase safeguards at both points of origin and entry for biosecurity against introduction from invasive fungal species in wood products. Future import regulations should consider living fungi, their tolerance to extreme conditions, and their potential survival in solid substrates. Mitigation efforts may require additional steps such as more stringent fumigation and/or sterilization strategies and limiting use of wood that has not been processed to remove bark and decay. IMPORTANCE This study, the first of its kind, demonstrates the risk of importation of nonendemic foreign fungi on wooden handicrafts into the United States despite the application of sanitation protocols. Previous risk assessments of imported wood products have focused on potential for introduction of invasive arthropods (and their fungal symbionts) or have focused on other classes of wood products (timber, wooden furniture, garden products, etc.). Little to no attention has been paid to wooden handicrafts and the fungal pathogens (of plants and humans) they may carry. Due to the large size and diversity of this market, the risk for introduction of potentially dangerous pathogens is significant as illustrated by the results of this study.